2020
DOI: 10.1039/d0ra07972c
|View full text |Cite
|
Sign up to set email alerts
|

The valorization of municipal grass waste for the extraction of cellulose nanocrystals

Abstract: The production of CNCs from MGW is an avenue to convert green waste into a value-added product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 66 publications
(69 reference statements)
0
10
1
Order By: Relevance
“…As the lignin content (29%) reported in this study (Table 2) is much higher than that reported in most studies: 14% (sisal fibers) [56], 9% (municipal grass waste) [21], and 9% (lemon seeds) [57], the use of acetic acid and formic acid in the pretreatment step was needed to increase the purity of cellulose and facilitate the removal of lignin as well as digestibility, and thereby enhance the whiteness of the pulps. However, in a preliminary work during extraction of cellulose from other lignocellulosic materials with low lignin content, the whiteness, cellulose content as well as the degree of crystallinity increased significantly without such additional step.…”
Section: Plos Onecontrasting
confidence: 59%
See 2 more Smart Citations
“…As the lignin content (29%) reported in this study (Table 2) is much higher than that reported in most studies: 14% (sisal fibers) [56], 9% (municipal grass waste) [21], and 9% (lemon seeds) [57], the use of acetic acid and formic acid in the pretreatment step was needed to increase the purity of cellulose and facilitate the removal of lignin as well as digestibility, and thereby enhance the whiteness of the pulps. However, in a preliminary work during extraction of cellulose from other lignocellulosic materials with low lignin content, the whiteness, cellulose content as well as the degree of crystallinity increased significantly without such additional step.…”
Section: Plos Onecontrasting
confidence: 59%
“…However, in a preliminary work during extraction of cellulose from other lignocellulosic materials with low lignin content, the whiteness, cellulose content as well as the degree of crystallinity increased significantly without such additional step. Different studies which employ sodium hydroxide in the pretreatment stage use chlorine containing bleaching agents mainly sodium chlorite solution [21,[57][58][59][60] during isolation of CNCs, however, a chlorine-free bleaching solvent (alkaline hydrogen peroxide) was employed in our study.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Acid hydrolysis is the most common type of this method used to date. The hydrolysis method reduces the sizes of nanofibres from microns to nanometres [76][77][78][79]. However, this method is not without drawbacks, such as the use of high concentrations of acid, which leads to acid waste and considerably adverse effects on the environment.…”
Section: Preparation Of Graphene Quantum Dots-nanocellulose Compositesmentioning
confidence: 99%
“…The use of this compound is spreading in many fields, including the biomedical, packaging and environmental sectors, thanks not only to its chemical and physical properties, but also as a renewable, sustainable and biodegradable material. [4][5][6] In this study we chemically isolate cellulose from wood to exploit another of its unique qualities: its record of atmospheric carbon content. 7,8 Through the photosynthesis process, atmospheric CO 2 is stored as carbon in plants.…”
Section: Introductionmentioning
confidence: 99%